The Implementation of Total Physical Response in Increasing Students’ Participation in Learning Vocabulary - Paramita, Putu Wahyu Gitari (English Education Department STKIP Agama Hindu Singaraja, 2022)
In acquiring a language, it should be considered that internal and external motivation hold the crucial place as the basic thing to support young learners’ willingness and attract them to have some interested in learning new language, such as learning English. This research has an aim to investigate the implementation of total physical response (TPR) in increasing students’ motivation in learning vocabularies by observing the second graders of SD Negeri 2 Kayuputih Melaka, Bali. TPR is a good method to teach new language for young learners. TPR is used to see how it affects students’ motivation to learn more English vocabularies. This study designed in form of qualitative research. The method being used to analyze the data belongs to descriptive qualitative. The result of this research indicates that the use of TPR is successfully increase students’ motivation to participate more in learning vocabularies. The students showed a significant knowledge of new vocabularies that had been learnt during the meetings shown by the chart being explained that shown the increment of students’ participation and new vocabularies achievement. The conclusion of this study is TPR positively works in increasing students’ participation in learning vocabularies for second graders at SD 2 Kayuputih Melaka.